Understanding hand sign language in human-computer interaction - Er, Alvin Beng Kiong (2009)
In this project, an English to American Sign Language translator cum American Sign Language learning application, Let’s Talk, had been successfully developed using the main character as Sydney, the 3-D human figure. The objective of this application is to use as a communication tool for the user to communicate with a hearing impaired person. The word or sentence for translation can be typed on the GUI using the keyboard or a speech recognition technology. Quiz is also implemented as a learning tool for the user.